The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.3858/bmbrep.2010.43.10.698
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility for breast cancer in young patients with short rare minisatellite alleles of BORIS

Abstract: In this study, we characterized two blocks of minisatellites in the 5' upstream region of the BORIS gene (BORIS-MS1, -MS2). BORIS-MS2 was found to be polymorphic; therefore, this locus could be useful as a marker for DNA fingerprinting. We assessed the association between BORIS-MS2 and breast cancer by a case-control study with 428 controls and 793 breast cancers cases. Rare alleles in the younger group (age, <40) were associated with a statistically significant increased risk of breast cancer (odds ratio, 4.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Because of the abnormal expression of BORIS in several cancers, the regulation of its expression is of great interest. In our previous study, two minisatellites (BORIS-MS1 and BORIS-MS2) and a CpG island (À1096 to À762 from the first ATG) were identified through the characterization of genomic DNA sequence upstream of the gene (Yoon et al, 2010). Regulation by methylation in the CpG island might be a major mechanism of gene regulation (Woloszynska-Read et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the abnormal expression of BORIS in several cancers, the regulation of its expression is of great interest. In our previous study, two minisatellites (BORIS-MS1 and BORIS-MS2) and a CpG island (À1096 to À762 from the first ATG) were identified through the characterization of genomic DNA sequence upstream of the gene (Yoon et al, 2010). Regulation by methylation in the CpG island might be a major mechanism of gene regulation (Woloszynska-Read et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…And we characterized BORIS-MS2 as having seven alleles containing a different number of repeat units in 428 cancer-free females and 793 breast cancer cases. As a result of this case-control study, we found that the short rare alleles of BORIS-MS2 were correlated with a high risk of breast cancer in younger patients (age, < 40 years) (Yoon et al, 2010) BORIS, a member of the cancer-testis antigen family, shows abnormal expression patterns in various cancers including breast cancer (D'Arcy et al, 2008). Furthermore, a prostate carcinoma revealed modestly increased BORIS expression compared to normal tissues (Hoffmann et al, 2006).…”
Section: Discussionmentioning
confidence: 77%
“…Previously, we described an association between variation in minisatellite lengths and cancer predisposition (Leem et al, 2002;Leem et al, 2004;Jeong et al, 2007;Seol et al, 2008;Yoon et al, 2008;Lee et al, 2009;Kwon et al, 2010). In a recent study, we observed that rare alleles of BORIS-MS2 in the younger group (age, < 40 years) were associated with a statistically significant increased risk of breast cancer (Yoon et al, 2010). Moreover, Kaplan-Meier estimates showed that poor prognosis was correlated with the age of patients that contained the short rare alleles (Yoon et al, 2010).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations